Prototyping of an Adaptive Structure based on Physical Conditions. (June 2013) - Kontovourkis, Odysseas; Phocas, Marios C.; Tryfonos, George
Latest advances in digital architectural design enable applications of computation and fabrication strategies for the development of adaptive mechanisms. Adaptive design processes, influenced by environmental and human related conditions, are only developed partially with regard to the design, fabrication, and multi-objective performance based context. The current paper proposes an adaptive design process that investigates the design of a kinetic structure emphasizing material behaviour, embedded technology and computation. In parallel, it allows design proposals to adapt or transform with regard to geometrical configuration and structural behaviour according to external and internal influences. An adaptive hybrid structure is developed at digital and physical prototype level, where its behaviour is examined in real time under the influence of physical conditions. The development is based on a holistic design approach driven by environmental and human activity related conditions, while focusing on the application of elastic materials and embedded technology.